Study on Developing a Solution for Drowsy Drivers in Vehicles - Daniel Varghese George, Mrs. S. Poornima, Tarun Kumar Reddy, Dr. M. Pushpalatha (International Journal of Advanced Science and Technology, 2020)
This paper depicts an eye following framework for languor identification of a driver. It depends on use of Eye Aspect Ratio. The framework cautions the driver if the (EAR) surpasses a pre-determined level through an alarm sound and if repeated more than thrice will take the control from the driver to to the installed arduuino.